Concepts Analysis of Poverty (Comparative Study of the Concepts of the Statistics Agency of North Sumatra Province and the Concepts of Islamic Economy) - Arif Riyukuri; Marliyah Suryadi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The concept is a multidimensional concept that has many views from several figures and institutions. The Central Statistics Agency (BPS) is of the opinion that people are said to be poor if their average monthly struggle score is below the poverty line, BPS classifies the poverty line into two components, namely the food poverty line (GKM) which is described by 52 product categories and the non-food poverty line. food (GKBM) where what is measured is the minimum need for housing, clothing, education and health. However, the measure of poverty in the Islamic economy is based on the fulfillment of basic needs such as food, clothing and housing as well as supporting needs such as spiritual needs.